The Relationship of Organizational Climate with Organizational Citizenship Behavior of Permanent Lecture Who Has Been Certified - Mahmudah, Ainun; Kurniawati P, Endah (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2013)
As someone who has been recognized professionalism through certification program and is supported by a positive organizational climate should already certified lecturer at UIN Maliki Malang able to contribute optimally match the capacity and competence. Organizational citizenship behavior is a behavior that is very much appreciated when performed by lecturers while there was no formal description for improving the effectiveness and viability of the organization. Based on the above research aims to: (1) determine the organizational climate in UIN Maliki Malang, (2) determine organizational citizenship behavior on lecturer who has been certified in UIN Maliki Malang, (3) determine the relationship of organizational climate with organizational citizenship behavior of permanent lecturer that has been certified in UIN Maliki Malang. This study used quantitative research paradigm, and what kind of research is correlational research. The sample used researchers that 25% of 255 lecturers (N=60). Data collection methods in this study using the questionnaire. Based on the analysis of the study obtained the following results: 15% lecturers assess existing organizational climate very conducive, 70% lecturers assess existing organizational climate off conducive, and 15% of lecturers assess existing organizational climate less conducive. For the lecturers organizational citizenship behavior get results 18,33% to have high lecturers organizational citizenship behavior, 58,33% to have middle lecturers organizational citizenship behavior, and 23,33% to have low lecturers organizational citizenship behavior. From the correlation test results correlation coefficient (rxy) between organizational climate to lecturers organizational citizenship behavior is 0.639 with a chance of error (p) = 0.000 at significant level of 0.05. It means that the acceptance of the hypothesis (Ha), which reads: "There is a positive relationship of organizational climate with organizational citizenship behavior of permanent lecturer who has been certified in UIN Maliki Malang, where progressively conducive organizational climate, hence excelsior also lecturers organizational citizenship behavior ".